Assessing commercial attractiveness and resilience of a plan for starting a new small business - Szreder, Jaroslaw; Walentynowicz, Piotr (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The purpose of the article is to present a method developed by the authors, intended to increase the likelihood and number of cases of developing a plan for starting a new business by budding entrepreneurs. This is because in practice there is a clear gap in this area. The study uses the authors' didactic and empirical experience, the method of analysis and synthesis of literature and Internet sources, and the method of didactic experiment. As a result of the process undertaken, a simplified business plan method was developed and preliminarily verified as a remedy to the problem of the low level of development of planning documents by novice entrepreneurs in the situation of their establishment of business activities. Since the results of the conducted experiment seem promising, the authors hope to disseminate and effectively use the method in practice. At the same time, as a result of the publication of the article, they hope for its review and further verification among experts in science and practice.